2022
DOI: 10.20491/isarder.2022.1450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dark Leadership on Organizational Commitment: A Research in The Banking Sector

Abstract: Purpose –The purpose of this study is to examine the impacts of dark leadership on organizational commitment. As opposed to the positive leadership styles’ benefits, it is expected to see a negative impact of the negative leadership styles on organizational commitment. Dark leadership is a term to describe the leadership in a context where the leaders’ negative personality traits negatively affect the organizational decision-making and the public impression of the organization.Design/methodology/approach –In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Contrary to what was defined, the results presented did not confirm the positive influence of perceived transformational leadership on normative commitment and continuance commitment (H3b,c). As pointed out by [78], given normative commitment and continuance commitment are linked to involvement based on moral duty, on the one hand, and the high costs associated with leaving, on the other hand, employees may be indifferent to the leader's actions. Despite this, the lack of a positive influence of perceived transformational leadership on continuance commitment is consistent with studies developed by [79].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to what was defined, the results presented did not confirm the positive influence of perceived transformational leadership on normative commitment and continuance commitment (H3b,c). As pointed out by [78], given normative commitment and continuance commitment are linked to involvement based on moral duty, on the one hand, and the high costs associated with leaving, on the other hand, employees may be indifferent to the leader's actions. Despite this, the lack of a positive influence of perceived transformational leadership on continuance commitment is consistent with studies developed by [79].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, it is believed that they are more competent and impressive than other people. However, many studies have shown that leaders are not just composed of positive, ideal characteristics (Conger, 1990;Başar et al, 2016;Bahadır and Çakırel, 2022;Özdemir and Karaçınar, 2022). They even have some dysfunctional dark faces.…”
Section: Discussionmentioning
confidence: 99%